"The Effect of Tax Burden and Tax Mix on Economic Growth: The Case of Egypt: A New Approach" - Abdel Qader, Metwally (The Arab Journal of Administration, 2022)
A nation’s tax structure has important consequences for the rate at which its economy grows. The main aim of this. study is to examine the effect of the tax burden and tax mix on the rate of growth of real GDP in Egypt for the period (1981: 2017). The tax burden is measured by tax revenues to real GDP and the tax mix is measured by indirect tax to direct tax. The aim of this study raises a number of questions. Is there a relationship between the rate of growth of real GDP and the tax structure (the tax burden and the tax mix)? If so, which component (the tax burden or the tax mix), has the more potent impact on the rate of growth? Is it possible to determine values of the tax burden and the tax mix that would maximize rate of growth? The objective of this study is to provide answers to each of these questions.The study uses a simple version of the standard neoclassical model of economic growth, in which taxes play an indirect role. On the other hand, a new approach has been implemented by using a relatively new statistical method that solves the omitted variables problem. In the first stage, we use a linear programming model in which the non-tax influences on economic growth are isolated. In the second stage, we use an econometric model in which taxes directly influence economic growth, independently of the non-tax factors which were isolated in the first stage. We calculate growth elasticities with respect to the tax burden and the tax mix, and we derive growth maximizing values of the tax burden and the tax mix.The study concluded that there is a positive and significant relationship between the change in the tax burden and the growth rate, while the effect of the tax mix was insignificant and neutral. However, the impact of the tax burden and the tax mix is negatively impacted by a large coefficient at their high levels. Elasticities of growth with respect to the tax burden and the tax mix has been positive for all the years. On average over the period, a 1% increase in the tax burden has 4 times as large impact on economic growth as does a 1% increase in the tax mix. The most important result is that the optimal mean of the tax burden and the tax mix values have exceeded the observed mean. The positive impact of the tax burden can be sustained and enhanced if the government established an effective and transparent tax system in such a way that increase the tax but it would not have an adverse effect on the economic growth